Examining The Influence of Entrepreneurial Education on Entrepreneurial Intention: Evidence from Postgraduate and Undergraduate Students with an Entrepreneurial Mindset as a Mediator (International Journal of Latest Technology in Engineering Management & Applied Science, 2026)
This study explores the impact of entrepreneurial education on entrepreneurial intention, with a focus on the mediating role of entrepreneurial Mindset among postgraduate students. The study aims to assess the reliability and validity of the key constructs—entrepreneurial education, entrepreneurial Mindset, and entrepreneurial intention—while also examining the predictive relationships among them through regression analysis. Data were collected from a sample of 203 postgraduate and undergraduate students enrolled in autonomous colleges affiliated to Mangalore University and deemed universities in Mangalore that offer Entrepreneurship as a compulsory course. Standardised scales were employed, and the analysis was conducted using SPSS. Reliability was confirmed through Cronbach’s alpha, while construct validity was established using factor analysis. Regression results indicate a positive relationship between entrepreneurial education and entrepreneurial intention, with entrepreneurial Mindset playing a significant mediating role. These findings provide preliminary support for the theoretical model and underscore the importance of fostering both educational and psychological components in nurturing entrepreneurial intent among students. The results also serve as a foundation for further large-scale empirical studies in this domain.